Long-Term Antibiotics in Bronchiectasis - Suarez-Cuartin, Guillermo; Hernandez-Argudo, Marta; Perea, Lidia; Sibila, Oriol (Seminars in Respiratory and Critical Care Medicine, 2021)
A significant proportion of bronchiectasis patients are chronically infected by potentially pathogenic microorganisms which may lead to frequent exacerbations and worse clinical outcomes. Current bronchiectasis guidelines recommend long-term inhaled antibiotics and/or oral macrolides as a part of patient management. In recent years, an increasing amount of evidence assessing the impact of these treatments on patient outcomes has been collected. Inhaled antibiotics have demonstrated significant improvements in sputum bacterial load, but their impact on patient quality of life, lung function, and exacerbation rate has not been consistent across trials. In this regard, recent post hoc analyses of inhaled antibiotics trials in bronchiectasis patients have shown that sputum bacterial load may be a key biomarker to predict treatment response in these patients. Oral macrolides, on the other hand, have proven to reduce exacerbation frequency and improve quality of life, but potential drug-related adverse effects and the increase in bacterial resistance are relevant. This review aims to summarize current important evidence for long-term antibiotic treatment in bronchiectasis patients.
Keywords: bronchiectasis; inhaled antibiotics; macrolides; exacerbations